Civic Education in Pre-Service Training Program for Teachers and Children Welfare Professionals - Giedrė Kvieskienė (Social Work & Society, 2006)
This article was designed to evaluate the effects of the Project Citizen and an innovative master's degree program aimed at preparing educators to address the social and academic needs of children in Lithuania. We the People...Project Citizen Materials [1] are an instructional product for adolescent students, which was developed and published in 1992 by the Center for Civic Education at Calabasas, California. The Project Citizen engages students in learning experiences designed to affect positively their civic development, which involves three basic components of democracy citizenship: civic knowledge, skills, and civic dispositions. In our opinion Civic Education and Democracy Schooling tradition should not only involve free, positive, and constructive participation of citizens in civic and political associations. We should and we can, on the one hand, ensure education of values, concept of social inclusion, social partnership, social capital and context of cultural diversity, which require willingness to participate in pluralistic political structures based on principles of justice and equitable distribution of material and symbolic resources. On the other hand, we analyze the civic education within the processes of social and political change. We consider that the essential role of the social educator is to provide general welfare for children and families as well as to foster the creation of school environments that can serve as places where teachers and students can experience democracy every day. In this article we explore how themes and concepts from civic education and social work fields have been woven together in this unique program to provide the foundation for its graduates to address the numerous challenges faced by children and families in contemporary Lithuania.